2015
DOI: 10.3109/09513590.2015.1056143
|View full text |Cite
|
Sign up to set email alerts
|

1-h Postprandial glucose level is related to the serum anti-Müllerian hormone level in women with polycystic ovary syndrome

Abstract: The aim of this study was to evaluate the relationship between the serum anti-Müllerian hormone (AMH) level and parameters related to insulin resistance in Korean women with polycystic ovary syndrome (PCOS). A total of 95 Korean women aged 18-33 years who were newly diagnosed with PCOS according to the Rotterdam Consensus at a university hospital were included in this study. Blood samples were collected from all participants during the early follicular phase using tubes without anticoagulants after an overnigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In the current study, we categorized all participants into three groups according to the LH/FSH ratio: group 1 (LH/FSH ratio <1.0), group 2 (1.0≤ LH/FSH ratio <2.0), and group 3 (LH/FSH ratio ≥2.0). In this study, participants with higher LH/FSH ratios showed higher total antral follicle counts and larger total ovarian volume, and these findings are in agreement with those of previous studies [1516222324]. …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, we categorized all participants into three groups according to the LH/FSH ratio: group 1 (LH/FSH ratio <1.0), group 2 (1.0≤ LH/FSH ratio <2.0), and group 3 (LH/FSH ratio ≥2.0). In this study, participants with higher LH/FSH ratios showed higher total antral follicle counts and larger total ovarian volume, and these findings are in agreement with those of previous studies [1516222324]. …”
Section: Discussionsupporting
confidence: 93%
“…Inappropriate gonadotropin secretion is one of the most characteristic hormonal features and is associated with the continuation of the anovulatory state in women with PCOS [15]. The abnormal gonadotropin secretion pattern in PCOS is characterized by increased serum LH levels and an increased LH/FSH ratio [4], and this pattern is related to increases in both the amplitude and frequency of LH secretion secondary to increased pulse frequency of hypothalamic gonadotropin-releasing hormone [819].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations